The authority of law in the Hebrew Bible and early Judaism tracing the origins of legal obligation from Ezra to Qumran - Vroom, Jonathan (Boston BRILL, 2018)
Intro -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- 1 Legal Obligation and the Ancient Near Eastern Law 'Codes' -- 2 Interpretation as the Key to Identifying Legal Obligation -- 3 Legal Theory and the Problem of Conceptual Anachronism -- 4 Overview of Chapters -- Part 1 Theory and Method -- Chapter 1 Identifying Legal Obligation in Interpretive Sources -- 1 Legal Obligation and the Nature of Law's Authority -- 2 The Rule of Law and Legal Interpretation -- 3 Sabbath Interpretation as a Test Case -- 4 Conclusion -- Chapter 2 History of Research and the Need for a Legal-Theoretical Approach -- 1 Arguments for the Non-Binding Character of Ancient Near Eastern Law -- 2 History of Scholarship and Conflicting Assumptions about Law -- 3 Conclusion -- Chapter 3 Authority and Problem of Interpretation -- 1 Defining Interpretation, Authority, and Scripture -- 2 Authority and the Problem of Interpretation -- 3 Authority Transfer and the Limits of Interpretation in Modern Law -- 4 Authority and Interpretation in Ancient Israel and Early Judaism -- 5 Interpretive Methods and Motives -- 6 Conclusion -- Part 2 Textual Analysis -- Chapter 4 Legal Interpretation in the Temple Scroll's Yom Kippur Law -- 1 An Overview of the Temple Scroll -- 2 The Text of Temple Scroll 25:10-27:10 -- 3 Threats to the Rule of Law Addressed in Temple Scroll's Interpretive Rewriting -- 4 Conclusion -- Chapter 5 Legal Innovation in the Samaritan Pentateuch's Covenant Code -- 1 The Provenance of the Samaritan Pentateuch's Legal Innovations -- 2 Correcting Threats to the Rule of Law in the Samaritan Pentateuch -- 3 Further Considerations -- 4 Conclusion -- Chapter 6 Legal Rewriting in the Qumran Penal Codes -- 1 The Literary Relationship among the Rule Texts and the Problem of Their Genre -- 2 Interpretive Rewriting in the Penal Codes
3 The Genre of the Penal Codes and Historical Reconstruction -- 4 Conclusion -- Chapter 7 The Authority of the Torah in the Ezra-Nehemiah Legal Narratives -- 1 Preliminary Issue: Ezra's Torah and Pentateuchal Law -- 2 Community Response as Reflecting a Binding Attitude toward Law -- 3 The Authority of the Torah versus Torah Experts in Yehud -- 4 Conclusion -- Conclusion -- 1 Summary of Theory and Method -- 2 Summary of Textual Analysis -- 3 Between Authority and Interpretation in Ancient Law -- 4 Mapping the Emergence of Legal Obligation in Early Judaism -- 5 Looking Ahead -- Bibliography -- Index of Ancient Sources -- Index of Modern Authors
Keywords: Hochschulschrift